The Application of Restorative Justice-Based Penal Mediation at the Batu District Attorney's Office : Penerapan Mediasi Penal Berbasis Keadilan Restoratif di Kejaksaan Negeri Batu - Wicaksono, Adhi Satyo (Rechtsidee, 2025)
General Background: Criminal justice reform in Indonesia increasingly emphasizes restorative justice as a humane alternative to retributive approaches, particularly through penal mediation. Specific Background: The issuance of Regulation of the Prosecutor’s Office No. 15 of 2020 mandates the optimization of penal mediation to resolve criminal cases by prioritizing victim recovery and social harmony, as implemented by the Batu District Attorney’s Office. Knowledge Gap: Existing studies largely focus on normative or philosophical dimensions of penal mediation, leaving limited empirical analysis on its practical implementation at the prosecutorial level. Aims: This study examines the application of restorative justice–based penal mediation at the Batu District Attorney’s Office, identifies implementation barriers, and formulates an ideal model for optimization. Results: Empirical findings reveal that penal mediation has been implemented in accordance with the regulation, resolving nine cases in 2024, yet faces obstacles including victim unwillingness, recidivism, compensation disputes, and limited procedural timeframes. Novelty: This research offers an empirical, practice-oriented analysis of restorative penal mediation within a district prosecutor’s office context, filling a gap in implementation-focused scholarship. Implications: Strengthening internal regulations, extending mediation time limits, and enhancing specialized training for prosecutors are crucial to ensure legal certainty, effectiveness, and sustainable restorative justice outcomes. Highlights: Implementation of restorative justice–based penal mediation aligns with Regulation No. 15 of 2020 but remains procedurally constrained. Practical barriers include victim resistance, recidivism, compensation disputes, and limited mediation timeframes. Institutional strengthening through internal regulations and specialized prosecutor training is essential for effective mediation outcomes. Keywords: Prosecutorial Authority, Penal Mediation, Restorative Justice, Criminal Case Resolution, Legal Reform